2021
DOI: 10.1021/acs.analchem.1c02040
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Imaging on Conductive Surfaces

Abstract: Electrochemical impedance spectroscopy (EIS) is a powerful tool to measure and quantify the system impedance. However, EIS only provides an average result from the entire electrode surface. Here, we demonstrated a reflection impedance microscope (RIM) that allows us to image and quantify the localized impedance on conductive surfaces. The RIM is based on the sensitive dependence between the materials' optical properties, such as permittivity, and their local surface charge densities. The localized charge densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…On the other hand, the accumulation of charges on the electrode surface will change the permittivity of the metal electrode surface and accordingly induce a decrease in the reflected optical intensity. Such EDL-effects have been previously observed by RIM in our previous work 44,45 . Zhou et al also reported the EDL established at the solid/liquid interface when the Cu electrode was charged to 1 V 33 .…”
Section: Formation Of Lif-rich Proto-seisupporting
confidence: 81%
“…On the other hand, the accumulation of charges on the electrode surface will change the permittivity of the metal electrode surface and accordingly induce a decrease in the reflected optical intensity. Such EDL-effects have been previously observed by RIM in our previous work 44,45 . Zhou et al also reported the EDL established at the solid/liquid interface when the Cu electrode was charged to 1 V 33 .…”
Section: Formation Of Lif-rich Proto-seisupporting
confidence: 81%
“…This is why we did not test higher voltage. However, the latter could be questionable as the optical properties of Au surface were reported to vary under applied potential [28]. Fig.…”
Section: Bmentioning
confidence: 99%
“…Recently, magnetic resonance imaging (MRI) has been employed to map the distribution of the water content within polymers, providing vivid information on the transport of water molecules in hydrogels. 18,19 In recent years, advanced optical imaging techniques have been rapidly developed to successfully image the physical and chemical properties of nanofilms, 20,21 single nanoparticles 22 and even single molecules due to their excellent sensitivity and high spatiotemporal resolution. 23 For example, Lu et al monitored the dynamic evolution of polymer-aging by specifically lighting up the aging products with a fluorescence microscope.…”
mentioning
confidence: 99%